2021
DOI: 10.1002/chem.202103587
|View full text |Cite
|
Sign up to set email alerts
|

N‐Aryl and N‐Alkyl Carbamates from 1 Atmosphere of CO2

Abstract: We have successfully isolated and characterized the zinc carbamate complex (phen)Zn(OAc)(OC(=O)NHPh) (1; phen=1,10‐phenanthroline), formed as an intermediate during the Zn(OAc)2/phen‐catalyzed synthesis of organic carbamates from CO2, amines, and the reusable reactant Si(OMe)4. Density functional theory calculations revealed that the direct reaction of 1 with Si(OMe)4 proceeds via a five‐coordinate silicon intermediate, forming organic carbamates. Based on these results, the catalytic system was improved by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…When Si­(OMe) 4 was used as an alkoxide source and dehydrating agent for the synthesis of CAEs in our previous study, some catalysts were required for efficient reactivity. , We also reported a reaction in which low-concentration CO 2 was captured by amines and DBU as carbamic acid salts that were subsequently reacted with Ti­(OR′) 4 to obtain CAEs . Therefore, considering that DBU would function as a catalyst and CO 2 adsorbent, we reacted low-concentration CO 2 with DBU and Si­(OMe) 4 without an additional catalyst.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When Si­(OMe) 4 was used as an alkoxide source and dehydrating agent for the synthesis of CAEs in our previous study, some catalysts were required for efficient reactivity. , We also reported a reaction in which low-concentration CO 2 was captured by amines and DBU as carbamic acid salts that were subsequently reacted with Ti­(OR′) 4 to obtain CAEs . Therefore, considering that DBU would function as a catalyst and CO 2 adsorbent, we reacted low-concentration CO 2 with DBU and Si­(OMe) 4 without an additional catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we have established a method for regenerating Si­(OR′) 4 from (R′O) 3 SiOSi­(OR′) 3 , which is the product of the reaction between Si­(OR′) 4 and H 2 O, using the corresponding alcohols . Furthermore, in the presence of Si­(OR′) 4 , a Zn­(II) complex catalyst, and a metal salt additive (KOMe or KF) under 1 atm of CO 2 N -aryl CAEs were obtained in high yields (81–98% for 12 examples) even at temperatures and reaction times lower than those reported in our previous studies (Scheme b) . However, pure CO 2 , a metal-complex catalyst, and an additive are essential to obtain high yields of CAEs in the above system.…”
Section: Introductionmentioning
confidence: 99%
“…We performed reaction mechanism analysis by experimental methods for the Zn(OAc) 2 /phen-catalyzed organic carbamate synthesis from CO 2 . 48 First, Zn(OAc) 2 , phen, and PhNH 2 were heated in MeCN under the assumption that the zinc catalyst activates the amine rather than CO 2 and Si(OMe) 4 ; however, the expected zinc amide complex 8 was not obtained (Scheme 10a). On the other hand, a similar reaction under CO 2 pressure yielded zinc carbamate complex 9 corresponding to the compound with CO 2 inserted into the Zn–N bond in 8 (Scheme 10b).…”
Section: Alkoxysilanesmentioning
confidence: 99%
“…In this paper, we review several examples of our previously reported regenerable reagents, namely tin alkoxides, 42 titanium alkoxides, 43,44 and alkoxysilanes (Scheme 3d). [45][46][47][48]…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, organic carbamates have attracted much attention from the synthetic community due to their diverse interesting properties. In addition to being an important class of privileged structures in pharmaceuticals in the forms of drugs and prodrugs, the carbamate motif is also broadly existed in agrochemicals and polymers. The most common methods to organic carbamates rely on the nucleophilic addition of alcohols to isocyanates or isocyanate intermediates generated in situ form acyl azides via Curtius rearrangement (Scheme ). In addition, the utilization of CO 2 , ,, CO, , or COCl 2 as C1 synthon to combine with amines and alcohols provides an alternative convenient access to organic carbamates. Very recently, some supplementary strategies have also been developed through transition metal-catalyzed or novel rearrangement process. …”
Section: Introductionmentioning
confidence: 99%